Changing Disease Prevalence, Incidence, and Mortality Among Older Cohorts: The Health and Retirement Study. (13th November 2019) - Crimmins, Eileen M; Zhang, Yuan S; Kim, Jung Ki; Levine, Morgan E
Abstract: Background: This article investigates changes in disease prevalence, incidence, and mortality among four cohorts of older persons in the Health and Retirement Study. Methods: We examine two cohorts initially aged 51 to 61, whom we call younger cohorts, and two older cohorts aged 70 to 80 at the start of observation. Each of the paired cohorts was born about 10 years apart. We follow the cohorts for approximately 10 years. Results: The prevalence of cancer, stroke, and diabetes increased in later-born cohorts; while the prevalence of myocardial infarction decreased markedly in both later-born cohorts. The incidence of heart disease, myocardial infarction, and stroke decreased among those in the later-born older cohort; while only the incidence of myocardial infarction decreased in the later-born younger cohort. On the other hand, diabetes incidence increased among those in both later-born cohorts. Death rates among those with heart disease, cancer, and diabetes decreased in the later-born cohorts. The declining incidence of three cardiovascular conditions among those who are over age 70 reflects improving population health and has resulted in stemming the increase in prevalence of people with heart disease and stroke. Discussion: While these results provide some important signs of improving population health, especially among those over 70; trends for those less than 70 in the United States are not as positive.